The relationship between sleep and autonomic health. Issue 5 (3rd July 2020) - Oliver, Michael D.; Baldwin, Debora R.; Datta, Subimal
Abstract: Objective: To examine the relationship between sleep and resting autonomic nervous system (ANS) functioning in college students. Participants: Participants were 141 undergraduate students (52 males) recruited from a large southeastern university during September–October 2017. Methods: Participants completed self-report inventories (demographic and sleep characteristics). Resting state skin conductance (SC) and heart rate variability (HRV) were measured in a laboratory setting for ANS functioning. Results: SC was positively associated with sleep quality ( p = 0.027), sleep latency ( p = 0.040), and use of sleep medication ( p < 0.001). Analyses yielded a negative association between the standard deviation of the normal-normal interval of heart beats (SDNN) and the self-reported amount of time to fall asleep each night ( p = 0.041). Sleep efficiency was negatively correlated with low frequency HRV ( p = 0.002). Conclusions: Sleep components are associated with resting ANS activity, and targeted interventions focused on improved ANS functioning may benefit sleep quality in college students.